การศึกษาการใช้หลักสูตรก่อนประถมศึกษา พุทธศักราช 2540 ในโรงเรียนประถมศึกษา สังกัดสำนักงานการประถมศึกษากรุงเทพมหานคร - วิไลพร เรือนศรี (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
The purpose of this study is to study the implementation of preschool curriculum B.E.2540 in elementary schools under the Office of Bangkok Primary Education. The research covered the curriculum administration and the implementation of learning activities according to the curriculum. The samples were 271 persons which comprised of 68 administrators and 203 preschool teachers. The results indicated that on the curriculum administration, 1) most of elementary schools planned to develop the activities appropriate to age, interest, need and individual differences of the children. And they nurtured and provided the experiences for developing the children to the right way. 2) For personnel preparation, the administrators considered experienced teachers to teach in the preschool class and the proportion of teacher per children was 1 : 21-30. The classroom teachers were sent to join the curriculum implementation seminars in order of use the knowledge from them to manage activities for children. In addition, the parents were oriented about the knowledge and understanding on curriculum implementation. 3) The preschool curriculum B.E.2540 by the Academic Department and the manual of the preschool curriculum B.E.2540 (the age of 3-6 years) by the Academic Department were provided to the classroom teachers. 4) For media service, the administrators assigned the classroom teachers survey media, play instruments and learning materials for the activities and then report these information to the administrators. For choosing the media, the teachers would consider the appropriation of the age of children. 5) For building management and local academic resources, the surrounding were managed to according of curriculum implementation and regarded to learning atmosphere, cleanliness, safety and building using preparation. In the same time, the teachers used external knowledge resources to join learning for children. 6) For supervising and follow-up, the preschool teachers attended the meeting for conversing about the problems of curriculum implementation. 7) For the public relation of the curriculum, it was informed to the parents about ways and activity management. On the instructional management, 1) the administrators provided the curriculum documentaries to the teachers for using them to plan the activities. 2) There were the appropriate activity planning for the children. 3) All the teachers planned the activities according to the daily activity tables to children developments especially their fine motor. 4) Teacher used real media and natural materials for managing instructional activities. 5) The teachers measured and evaluated the children by observing and note - taking. The encountered problems were: the school lacked of budget in supporting the curriculum implementation; and teachers who graduated in early childhood education.